Understanding the concept of agentic engagement for learning - Montenegro, Aida (Colombian Applied Linguistics Journal, 2017)
Bearing in mind that agentic engagement has a recent history in comparison to the other types of engagement (behavioral, emotional and cognitive), this paper will present a theoretical review of this concept, including the reasons it has been denominated as the fourth type of student engagement. Agentic engagement is understood as the observable classroom event in which the learner constructively contributes to his/her learning and the instruction he/she receives (Reeve, 2012). The revision of research and theory on agentic engagement included in this paper supports the idea that it provides a consistent researchable field. Future research contributions may focus on (1) the disaffected face of agentic engagement, its conceptualization and its effects (Reeve & Tseng, 2011; Reeve, 2013) and (2) the understanding (description, typology, and analysis) of students’ self-initiated contributions (proactive actions) in the classroom (Waring, 2011) in order to identify which strategies may facilitate students’ learning processes, teacher’s agentic engagement interventions, and student-teacher interaction.